The impact of the split share structure reform on the information environment in China: evidence from analyst forecast properties, share price synchronicity and the value relevance of earnings - Ghazali, Muhammad Yahya (2019)
Over the last three decades, China has initiated several reforms in an attempt to transition itself from a socialist economy towards a more market-oriented economy. During the transition process, the Communist party promoted the development of financial markets that led to the re-establishment of the Shanghai and the Shenzhen stock exchange in 1990 and 1991. These stock markets, however, were based on the split share structure, which divides the total outstanding shares of a listed firm into tradable shares and non-tradable shares. Until 2005, around 70% of listed firm shares were non-tradable and were mainly held by the state (Liu and Tian, 2012).